Intermediality in the Novel “The Sellout” by Paul Beatty - Mosiievych, Larysa; Kurbatova, Tetiana; Prihodko, Ganna; Prykhodchenko, Oleksandra; Bondar, Iryna (Forum for Linguistic Studies, 2025)
This paper explores the linguistic realization of intermediality in Paul Beatty’s novel “The Sellout” and its role in creating satire and critiquing racial and cultural stereotypes. Intermediality, understood as references to music, cinema, and other art forms, is analyzed on explicit and implicit levels. The research aims to identify textual markers of intermediality, examine lexical and semantic groups, explore stylistic devices used for satire, and investigate conceptual metaphors that link art forms to the novel’s broader themes. It employs literary analysis, lexical and semantic analysis, stylistic analysis, and conceptual analysis. These methods reveal how intermediality contributes to both the narrative’s depth and its satirical tone. The findings show that intermediality grounds the novel in contemporary American culture, criticizes the commodification of African American identity in popular media, and exposes the role of pop culture in reinforcing social inequalities. Explicit intermedial references create humour and satire through stylistic devices like similes, bathos, and antitheses. Implicitly, intermediality uses conceptualizations of cinema and music to explore the themes of power, memory, and illusion. This study demonstrates that intermediality in The Sellout enriches its narrative complexity, amplifies its satirical impact, and challenges readers to critically evaluate societal norms. The paper is intended for a wide range of readers and specialists in literature and linguistics. It adds to expanding interdisciplinary research on intermediality, providing fresh perspectives on how contemporary literature integrates and reshapes different art forms to develop intricate and multi-dimensional narratives.